Teachers’ classroom instruction reinforcement strategies in english language class - Sri Wuli Fitriati; Devi Fatmala; Agung Ginanjar Anjaniputra (Journal of Education and Learning (EduLearn), 2020)
In the context of this study, reinforcement is an act of teachers to strengthenvstudents’ positive behaviour in learning English in the classroom. This qualitative case study was a classroom discourse which employed necessary quantification. The aim was to investigate the use of classroom instruction reinforcement strategies by two English language teachers and their perceptions at a state secondary school in Semarang in the academic year of 2019. The two English teachers were observed in five different lessons. The teachers were interviewed to explore their perceptions of using reinforcement in the classroom. The instruments of this study were observation sheet, interview guideline, and audio-video recordings. The findings showed that the teachers reinforced the students in three types of classroom instruction reinforcement. The three types of reinforcement strategies were: praise or other verbal reinforcement, tangible rewards, and token rewards. The reinforcement strategy mostly used was praise, followed by tangible rewards and token rewards. Based on the interviews, the teachers perceived that giving positive reinforcement to the students was important. The findings suggest the teachers implement the reinforcement strategies fairly to increase teacher-students interaction.